A descriptive study of the financial benefits of dental insurance - Hao, Elaine Lyn U.; Javier, Peter John (Adviser).
The price of good oral health is much too high to pay in the time of economic depression in the Philippines. The primary purpose of the study was present the financial benefit of patients acquiring dental insurance. This was achieved by identifying the cost of dental insurance premiums and their corresponding compensated services. The lowest possible price charged by the affiliated dental offices of selected insurance agencies for patients not covered by dental insurance was determined. A cost-benefit accounting was made to determine the difference in costs between the two payment options. From October 1999-September 2000, 91.3% of the insured population of the study gained an average of Php295.22. About 76% of the insured population gained an average of Php149.49 from all the years they are insured. Based on the data gathered and the analysis, it can be concluded that: It is financially beneficial to acquire dental insurance.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Insurance, Dental